Targeted liposomal nano-therapy combining anthocyanin and cisplatin reduces Ehrlich ascites carcinoma burden - Awad, Mai G.; El-Shafiey, Sara H.; Ali, Ramadan A.; Abd El-Monem, Dalia D.; Badawy, Abdelnaser A.; Al-Serwi, Rasha Hamed; El-Magd, Mohammed A.; Hanafy, Nemany A. N. (Frontiers in Pharmacology, 2025)
BackgroundEhrlich ascites carcinoma (EAC), a rapidly growing tumor model, poses challenges in chemotherapy due to toxicity and resistance. Liposomal drug delivery improves anticancer therapy by enhancing bioavailability, targeting, and reducing systemic toxicity. Cisplatin (Cis), although effective, induces severe hepatic and renal toxicity. Anthocyanins (Ant), natural flavonoids with antioxidant and anticancer activities, can synergize with chemotherapy and reduce toxicity. This study evaluated three nano-liposomal formulations for EAC: Ant-loaded liposomes (Ant Ls), Cis-loaded liposomes (Cis Ls), and their combination (Cis + Ant Ls).MethodsNano-liposomes containing Cis and/or Ant were prepared by thin-film hydration, functionalized with folic acid for targeting, and characterized by TEM for size and morphology. Encapsulation efficiency and drug release (48 h, dialysis) were determined. Cytotoxicity was tested on HCT 116 and Vero cells (MTT assay). Serum biochemical markers (ALT, AST, urea, and creatinine) were quantified, while tumor tissues were analyzed for apoptotic (caspase-3, Bcl2), inflammatory (IL1β), angiogenic (VEGF), metastatic (MMP9), and antioxidant (Nrf2, HO-1) genes using qPCR.ResultsAnt Ls demonstrated a high encapsulation efficiency of 93.06% and exhibited sustained release profiles, achieving the highest cumulative drug release of 59.11% at 48 h. Cis Ls and/or Ant Ls demonstrated significant cytotoxic (P < 0.05) effects on HCT 116 colon cancer cells while exhibiting minimal toxicity to normal Vero cells. In comparison to untreated EAC controls, mice treated with Cis Ls and/or Ant Ls exhibited significantly (P < 0.05) enhanced liver and renal function and structure, as evidenced by reductions in ALT, AST, urea, and creatinine and histopathology lesions. The treatments also decreased EAC burden as noticed by a reduction in total and viable tumor cell counts, and ascitic fluid volume, along with an increase in non-viable cells. The anticancer effect of Cis Ls and/or Ant Ls was attributed to multiple mechanisms, including increased apoptosis, reduced inflammation, inhibited angiogenesis, and suppression of metastasis. The combined treatment enhanced antioxidant defenses to mitigate Cis toxicity. The combination of Cis Ls and Ant Ls markedly decreased tumor burden and demonstrated therapeutic synergy, suggesting potential for improved outcomes.ConclusionCis Ls and Ant Ls delivery strategy mitigates liver and kidney damage while enhancing anticancer efficacy against EAC.